Interrelation of cardiovascular pathology and periodontal disease - Vitovsky, R. M.; Mazur, I. P.; Slobodyanik, M. V.; Martyshchenko, I. V. (Ukrainian Journal of Cardiovascular Surgery, 2018)
The article contains a review of literature on current views on the etiology and pathogenesis of inflammatory diseases of periodontal tissues, their relationship to the pathology of the cardiovascular system. Presented modern data on the role of parodontopathogenic microflora in the initiation and development of cardiovascular diseases. Pathogenetic link, which strengthens the connection between cardiovascular pathology and periodontal tissue diseases, is a systemic inflammatory reaction. The conjugate course of somatic and dental pathology requires joint efforts from dentists and cardiologists to prevent common risk factors.